Single-Cell Transcriptomic Sequencing Analyses of Cell Heterogeneity During Osteogenesis of Human Adipose-Derived Mesenchymal Stem Cells. (16th August 2021) - Qu, Rongmei; He, Kai; Fan, Tingyu; Yang, Yuchao; Mai, Liyao; Lian, Zhiwei; Zhou, Zhitao; Peng, Yan; Khan, Asmat Ullah; Sun, Bing; Huang, Xiaolan; Ouyang, Jun; et al.
Abstract: Mesenchymal stem cells (MSCs) are known for their multilineage differentiation potential with immune-modulatory properties. The molecular underpinnings of differentiation remain largely undefined. In this study, we investigated the cellular and molecular features of chemically induced osteogenesis from MSC isolated from human adipose tissue (human adipose MSCs, hAMSCs) using single-cell RNA-sequencing (scRNA-seq). We found that a near complete differentiation of osteogenic clusters from hAMSCs under a directional induction. Both groups of cells are heterogeneous, and some of the hAMSCs cells are intrinsically prepared for osteogenesis, while variant OS clusters seems in cooperation with a due division of the general function. We identified a set of genes related to cell stress response highly expressed during the differentiation. We also characterized a series of transitional transcriptional waves throughout the process from hAMSCs to osteoblast and specified the unique gene networks and epigenetic status as key markers of osteogenesis. Abstract : We investigated chemically induced osteogenesis from human adipose mesenchymal stem cells, human adipose mesenchymal stem cells (hAMSCs) using single-cell RNA-sequencing (scRNA-seq). We identified the cellular heterogeneity and their molecular and network regulatory pattern of osteogenic differentiation.